Projekty autostrad morskich w aspekcie zrównoważonego rozwoju transportu - Urbanyi-Popiołek, Ilona (Projects of the Sea Motorways in the Aspect of Sustainable Development in Transport, 2008)
The concept of sea motorways is connected with transport policy and the strategy of sustainable development of transport in the European Union. The development of short sea shipping and Trans-European Transport Network are very important in this strategy. The sea motorways are one of the main parts both of short sea shipping and TEN-T. The projects of the sea motorways must be proposed by at least two member states, concern the smallest possible number of ports and alleviate road traffic congestion on the main axes. Such a motorway consists of shipping services of high frequency and short transit time. A port should be equipped with an efficient infrastructure and a logistic system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 209-215